2020
DOI: 10.3390/s20010314
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Methodology in a System Applying the Adaptive Strategy for Teaching Human Motions

Abstract: The teaching of motion activities in rehabilitation, sports, and professional work has great social significance. However, the automatic teaching of these activities, particularly those involving fast motions, requires the use of an adaptive system that can adequately react to the changing stages and conditions of the teaching process. This paper describes a prototype of an automatic system that utilizes the online classification of motion signals to select the proper teaching algorithm. The knowledge necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 46 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…Recently, deep learning models, based on various variants of neural networks, such as CNN [ 26 ], RNN [ 27 ] or GNN [ 28 ], are also experiencing a renaissance. Depending on the area and specificity of applications, very complex approaches are used, often utilising integration and combination of many techniques, which is particularly visible in case of interdisciplinary problems occurring, for example, in such selected fields as medicine [ 29 , 30 ], education [ 31 , 32 ], metrology [ 33 , 34 , 35 ], biometrics [ 36 , 37 ], learning of motor activities [ 38 , 39 ] or gesture recognition [ 40 , 41 ].…”
Section: Ann-based Methods To Remove Artefactsmentioning
confidence: 99%
“…Recently, deep learning models, based on various variants of neural networks, such as CNN [ 26 ], RNN [ 27 ] or GNN [ 28 ], are also experiencing a renaissance. Depending on the area and specificity of applications, very complex approaches are used, often utilising integration and combination of many techniques, which is particularly visible in case of interdisciplinary problems occurring, for example, in such selected fields as medicine [ 29 , 30 ], education [ 31 , 32 ], metrology [ 33 , 34 , 35 ], biometrics [ 36 , 37 ], learning of motor activities [ 38 , 39 ] or gesture recognition [ 40 , 41 ].…”
Section: Ann-based Methods To Remove Artefactsmentioning
confidence: 99%
“…The creation of specialized learning algorithms is another important problem, which must be performed with the participation of experts [8], [10]. However, the experts might not necessarily perceive critical relationships between the aspects of the automatic teaching process, and generally may be unprepared for the challenges of creating new, unconventional algorithms of teaching.…”
Section: Learning Methods and The Role Of Expert Knowledgementioning
confidence: 99%
“…The authors of the last two papers suggested analyzing the current teaching context in order to change the teaching method accordingly (however, they did not propose specific methodologies). A system that used the results of the motion signal classification in the task of learning a trajectory, was described by Wójcik and Piekarczyk [10]. The authors concluded however, that, due to a problem with the system-learner communication, the proposed approach was not suitable for teaching fast movements.…”
Section: A the Learning Of Human Motion Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[17]. Based on BD personalization and adaptation, Wójcik and Piekarczyk examined the learning process structure, learning process visualization, and learning effect demonstration, and the findings showed that data analysis of students' learning behavior and knowledge mastery could recommend reasonable learning paths and learning resources with appropriate difficulty [18]. According to Z. Li et al, students' mastery of objective and subjective questions is linked and compensated in different ways [19].…”
Section: Introductionmentioning
confidence: 99%